When Women Owe Women: Framing Consumer Responsibility in the Context of Fast Fashion - Kathleen Horton; Paige Street; Erin O’Brien (International Journal for Crime, Justice and Social Democracy, 2022)
The consumer is an important political subject in addressing global social issues, especially in the fashion industry. Due to the complex, multi-jurisdictional nature of the problems created through global capitalism, a significant overhaul of the fashion industry is not easy to achieve; nor is it easy for consumers to choose to withdraw from these markets. Further, framing individual consumer responsibility is difficult, especially when considering how questions of obligation intersect with geographical hierarchies as well as questions of privilege.